Epigenetic Mechanisms Link Maternal Diets and Gut Microbiome to Obesity in the Offspring - Li, Yuanyuan (Frontiers in Genetics, 2018)
Nutrition is the most important environmental factor that can influence early developmental processes through regulation of epigenetic mechanisms during pregnancy and neonatal periods. Maternal diets or nutritional compositions contribute to the establishment of the epigenetic profiles in the fetus that have a profound impact on individual susceptibility to certain diseases or disorders in the offspring later in life. Obesity is considered a global epidemic that impairs human life quality and also increases risk of development of many human diseases such as diabetes and cardiovascular diseases. Studies have shown that maternal nutrition status is closely associated with obesity in progenies indicating obesity has a developmental origin. Maternal diets may also impact the early establishment of the fetal and neonatal microbiome leading to specific epigenetic signatures that may potentially predispose to the development of late-life obesity. This article will review the association of different maternal dietary statuses including essential nutritional quantity and specific dietary components with gut microbiome in determining epigenetic impacts on offspring susceptibility to obesity.